'From cloud to the board' - identification of triggers adoption in Brazilian companies. (26th November 2021) - Pinochet, Luis Hernan Contreras; Alves, Fabiana Robles Rodrigues; Lopes, Evandro Luiz; Herrero, Eliane; Brelàz, Gabriela De
This article analyses direct and indirect effects of the behavioural intention on the perception of managers of companies located in Brazil for the use of cloud computing technology. The main contribution of this study is to understand how companies accept and encourage the use of this technology and how users relate to this new mechanism. The theoretical model used was adapted from Wu (2011), with extension to various models of cloud computing delivery. This empirical research was carried out through a survey, consisting of a sample of 307 managers who play key roles in IT decisions in companies in Brazil. The results demonstrated that there is greater concern with skills that managers and users must possess for the use of cloud computing technology, as well as aspects related to the influence that the market has on the acquisition of new solutions.